#TITLE_ALTERNATIVE# - TARIH RAHMAN (NIM 15106066); Pembimbing: Dr. Irwan Meilano, ST, M.Sc., dan Irwan Gumilar, ST, ADHITA
The west of Sumatra region is a highly vulnerable region to earthquakes because of it's position along the path of two tectonic plates, subduction of Indo-Australian and Eurasian plates. Simeulue Earthquake Mw 7.4 on 20 February 2008 was occurred as the result of the movement Indo-Australian Plate subduct into under the Eurasian Plate. One effort that we can do to understand the earthquake occurance mecanism is to conduct coseismic deformation study that accompany the earthquake. By utilizing the GPS technology with high precission, so the occurrence of coseismic deformation can be detected on the earth surface which is shown by the response of displacement position from GPS stations in a certain time period. Based on the time series analize observation data from GPS stations, we can calculate the coseismic displacement vectors that happend due to the earthquake.